DEVELOPING STUDENTS’ READING COMPREHENSION BY USING SQ3R METHOD - Nian Masna Evawati (Politeknik Negeri Sriwijaya, 2010)
The objective of this study was to see whether or not SQ3R method can give a significant contribution to develop the reading comprehension at the second semester students of Chemical Engineering of State Polytechnic of Sriwijaya. For this purpose, a quasi experimental design was used. The subjects involved in this study were 54 second semester students of Chemical Engineering, in academic year of 2007/2008. The primary data were obtained by means of tests. These data were analyzed by using t-test. The result shows that there was a significant difference of student’s reading achievement before and after the treatment. The value of both groups (t) was higher (4.76) than the value of t-table which is 2.042. It is also found that the significant change made by the students in group 2 (experimental) was higher than group 1 (control). It can be seen that the result of the gained t of the group 2 was 8.618 whereas the gained t of the group 1 was 2.885. Both of groups’ value were higher than the value of the t table.